Arthroscopic Fixation of Osteochondral Avulsion Fracture of the Femoral Attachment of the Posterior Cruciate Ligament in an 82-Year-Old Patient: A Case Report. (8th September 2018) - Ishikawa, Masakazu; Kobayashi, Kenji; Adachi, Nobuo
Femoral avulsion fracture of the posterior cruciate ligament (PCL) is less common compared to the tibial side. Especially, femoral avulsion in an elderly patient is an extremely rare condition. Until now, there is no report that describes its treatment and clinical outcome in elderly patients. We demonstrate an 82-year-old female who presented with osteochondral avulsion fracture of the femoral attachment of the PCL. The osteochondral fragment was fixed with an arthroscopic transfemoral suture technique. After treatment, the pain was improved and the patient achieved previous daily activity within 6 weeks. After 6 months, plain X-ray and computed tomography scans demonstrated consolidation of osteochondral fragment. The Lysholm score was 78 points at final office visit. This simple and less invasive approach is useful for pain relief and earlier return to daily activity in an elderly patient with osteoporosis.